Characteristics of toluene decomposition and adsorbent regeneration based on electrically conductive charcoal particle-triggered discharge. Issue 71 (19th September 2017) - Xiao, Gang; Xu, Weiping; Luo, Zhongyang; Pang, Hua
Abstract : Electrically conductive charcoal particle-triggered discharge facilitates the desorption of adsorbed toluene and also decomposes ∼60% of the adsorbed toluene. Abstract : Volatile organic compounds (VOCs) are detrimental to human health, and are also among the most important causes of secondary particulate formation and ozone pollution. The combined method of adsorption and non-thermal plasma has been attracting increasing interest due to its efficient energy consumption. This study aims to explore a new approach for removing gaseous toluene using electrically conductive charcoal (ECC) as an adsorbent and to trigger discharge. ECC was prepared from biomass and had a low electrical conductivity of 0.354 Ω cm and an abundant porous structure with a surface area of 717 m 2 g −1 . After toluene adsorption (53–217 mg g −1 ), adsorbent particles were fluidized with oxygen-containing gas and subjected to high voltages (17.4–26.3 W). Micro-arcs formed between the fluidized ECC particles, which led to toluene desorption and decomposition while the ECC was regenerated. The desorption was facilitated compared to thermal desorption. The adsorbed toluene was almost completely desorbed, and 59.23% of toluene was decomposed at one time. Almost no ozone or nitrogen oxides were found in the gas produced from decomposed toluene. Higher adsorption and discharge power were beneficial for decomposition capacity, but the former was limited by short residence time. The adsorption capacity of ECC increased by 16.4% after four cycles. A design was presented for continuous treatment of VOC pollutant without the emission of VOCs.